2015
DOI: 10.1007/s00380-015-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistent pulmonary hypertension after mitral valve replacement

Abstract: Persistent pulmonary hypertension (P-PH) after mitral valve replacement (MVR) leads to an increased risk of morbidity and mortality. We sought to determine which factors were involved in its occurrence. Patients undergoing MVR for a 3-year period were collected in a retrospective way. We excluded those with an available follow-up shorter than 3 months. Sample size was 111 patients. PH was diagnosed if systolic pulmonary artery pressure (sPAP) estimated by Doppler echocardiography was >40 mmHg. Clinical, echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
4
26
0
3
Order By: Relevance
“…From our standpoint, the explanation may reside in the fact that significant tricuspid regurgitation following a left-sided heart disease is an independent risk factor encompassing several other factors such as pulmonary arterial hypertension and dyspnea. Such finding has been reported in several studies of other diseases with regard to aortic and mitral valve diseases which also corroborate the present data embodying multiple diseases at once[ 23 - 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…From our standpoint, the explanation may reside in the fact that significant tricuspid regurgitation following a left-sided heart disease is an independent risk factor encompassing several other factors such as pulmonary arterial hypertension and dyspnea. Such finding has been reported in several studies of other diseases with regard to aortic and mitral valve diseases which also corroborate the present data embodying multiple diseases at once[ 23 - 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…This high prevalence of preoperative PHT was expected, as the presence of significant TR may increase PASP irrespective of the left heart valve status. In the same context, prior reports have shown that the prevalence of postoperative residual PHT varies according to different types of valve surgery: 5% to 13% in patients who undergo mitral valve repair19, 20 and over 40% in those who undergo mitral valve replacement 21. Nonetheless, the prevalence of residual PHT in patients undergoing TA has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Целесообразность хирургической денервации симпатических сплетений в легочных артериях также продемонстрирована в работе S. Briongos Figuero и соавт. [29], которые показали, что высокая степень вторичной ЛГ в дооперационном периоде тесно коррелирует с высокой стойкой ЛГ в послеоперационном периоде даже после коррекции порока митрального клапана (отношение шансов 1,761; p=0,03). Методики хирургического лечения ЛГ применяются также в условиях искусственного кровообращения при одномоментной коррекции клапанной патологии сердца, которые заключаются в эпикардиальной абляции передней стенки ствола и устьев легочных артерий с применением монополярного электрода-ручки [30], а также методики циркулярной абляции ствола и устьев легочных артерий с применением биполярного деструктора [13,31].…”
Section: автор для перепискиunclassified